Kinetika adsorpsi mikrokapsul kitosan taut silang kalium persulfat terhadap zat warna methyl orange - Endang Sulistyawati; Wibiana Wulan Nandari; Arifa Rahma Nurchasanah; Kurnia Kumala Dewi (Jurnal Rekayasa Proses, 2020)
Dyes, typically available in textile and paper industries, can cause an aesthetical issue in their wastewater stream even in its low concentration Some colors are considered toxic to the environment and even carcinogenic. In that sense, the adsorption using chitosan, might be an alternative method offering better environmental quality by its capability for eliminating the dyes from the waste stream. This research was aimed to study the adsorption kinetics of methyl orange dyes in the presence of chitosan microcapsules, employing the measurement of concentration concerning time over several measured temperatures of 40, 50, and 60 °C. Chitosan microcapsules originated from abundantly available organic materials, have been synthesized by the support of potassium persulfate as a cross-linker through ionic gelation and solvent evaporation method. The microcapsules were subjected to Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) characterizations, while UV-Vis was utilized for observing dye concentration changes. The results showed that chitosan microcapsules had been successfully prepared with a deacetylation degree of 53.92 % and a grain diameter of 1246 μm. The adsorption adapted the chemisorption mechanism with endothermic behavior. Besides, its kinetics seemed to follow the Lagergren pseudo-second-order equation with the value of the kinetic constant suitable for the tested temperature, following the Arrhenius equation.